IMPLEMENTATION OF CHILD-FRIENDLY CARE IN PESANTREN - Abdurrahman Abdurrahman; Fathi Hidayah; Khabibatur Rohmah; Romi Ittaqi Robby; Rosyida Choulatul Jariyah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
In the pesantren, Kyai has high legitimacy regarding the pesantren's policies, especially in the program and process of caring for students (santri). This research aims to describe the implementation of child-friendly care in four pesantren in Malang Regency, namely PP. An-Nur 2 Al-Murtadlo, Al-Rifa'ie Modern Pondok, PP. Pesantren Rakyat Al-Amin, and PP. As-Syadzili. Analyzing the suitability of the implementation of child-friendly care with the latest regulations, the Decree of the Director General of Education, Ministry of Religion No. 1262 of 2024, and identifying factors that support and hinder the implementation of child-friendly care in pesantren. For this purpose, this research uses a multiple-case study method with replica logic. Four pesantrens were selected as samples by considering the diversity of types. Data was collected through observation, in-depth interviews with Kyai, managers, infrastructure, santri, and analysis of related documents. The data were analyzed using pattern matching and cross-case synthesis techniques. The research results show that implementing child-friendly care in the four pesantren s is optimal and following the indicators in the Technical Instructions. The management patterns of pesantren are formed in an organized manner with different models according to the needs and resources of each pesantren.